Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3855/jidc.1512
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and virulence genes of non-typhoidal Salmonella isolates in The Gambia and Senegal

Abstract: Introduction: The prevalence of virulence genes in non-typhoidal Salmonella (NTS) and its association with commonly used antibiotics in West Africa is unknown. Methodology: We tested 185 NTS isolates from children, animals, and food products for the presence of twelve virulence genes by PCR. Ten of the virulence genes tested belonged to the five Salmonella pathogenicity islands implicated in its pathogenesis. Results: Ten of twelve virulence genes except sopE and pefA were present in at least 70% of the isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 26 publications
8
32
1
3
Order By: Relevance
“…In this study, PCR assay was carried out for the detection of the invA gene from six isolated strains (S. enteritidis, S. macclesfield, S. rissen, S. derby, S. magherafelt and S. enterica sub.spp salamae) has revealed that the gene was present in all of the isolates (100%) that was demonstrated by the presence of a 284 bp PCR amplified fragment. The results obtained in the present study were in corroboration with [16]. PCR assay was carried out for the detection of the sopB gene from isolated strains has revealed that the gene was present in all of the isolates (100%) which was demonstrated by the presence of a 517 bp PCR product.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, PCR assay was carried out for the detection of the invA gene from six isolated strains (S. enteritidis, S. macclesfield, S. rissen, S. derby, S. magherafelt and S. enterica sub.spp salamae) has revealed that the gene was present in all of the isolates (100%) that was demonstrated by the presence of a 284 bp PCR amplified fragment. The results obtained in the present study were in corroboration with [16]. PCR assay was carried out for the detection of the sopB gene from isolated strains has revealed that the gene was present in all of the isolates (100%) which was demonstrated by the presence of a 517 bp PCR product.…”
Section: Discussionsupporting
confidence: 88%
“…This suggested a potential pathogenic role for these isolates, as they were associated with infection and diarrhea in most of these animals (GAL-MOR & FINLAY, 2006;JENNINGS et al, 2012). The virulence genes identified were similar to those detected in other Salmonella serovars isolated from humans and animals (DIONE et al, 2011;JENNINGS et al, 2012;PARVATHI et al, 2011). These results also suggested the presence of at least three Salmonella pathogenicity islands (SPIs) (IOANNIDIS et al, 2013) in these isolates since invA, Ramos et al orgA, prgH, sipB, and spaN are commonly encoded in SPI-1, spiA in SPI-2, and sopB in SPI-5 (DIONE et al, 2011;SKYBERG et al, 2006).…”
Section: Resultssupporting
confidence: 56%
“…The presence of Salmonella spp. was investigated using primers invA.F (5′- CTGGCGGTGGGTTTTGTTGTCTTCTCTATT -3′) and invA.R (5′- AGTTTCTCCCCCTCTTCATGCGTTACCC -3′) targeting the invasion gene invA [21]. For the detection of E.coli spp.…”
Section: Methodsmentioning
confidence: 99%